PEMBUATAN COOKIES DAUN MANGROVE (Rhizophora mucronata) DALAM UPAYA OPTIMALISASI PEMANFAATAN TANAMAN MANGROVE - Attaya, Kalisa; Maziya, Raehanul; Amalia, Marshanda Fitri; Bulkis, Nanda; Sutanti, Baiq Novia Rahmadita; Permatasari, Lina (Jurnal Pepadu, 2025)
An unhealthy lifestyle can lead to increased production of free radicals as a byproduct of metabolism. This condition can be mitigated by antioxidants. Rhizophora mucronata offers various health benefits, including its role as an antioxidant. However, public utilization of Rhizophora mucronata remains limited. To enhance its appeal, Rhizophora mucronata was processed into mangrove leaf cookies, making it more convenient for consumption. The objective of this activity was to optimize the utilization of mangrove plants. The activity was conducted on December 20, 2024, at the Meninting Village Hall, Batulayar Subdistrict, West Lombok Regency, with 20 participants. The implementation method included training sessions comprising the delivery of materials on mangrove plants and the process of making mangrove cookies, followed by hands-on cookie-making training. The participants were highly enthusiastic throughout the program, and the material was well understood, as evidenced by the quiz results provided during the session.